Unsteady aerodynamics and heat transfer in a transonic turbine stage - Ashworth, D (1987)
In current design methods for gas turbines there are important features of the flow which are not yet within the scope of the available prediction methods for both the calculation of surface pressures and heat transfer rates. Such features include the prediction of three-dimensional viscous flowfields, the accurate location and strengths of the secondary flow regimes in a turbine passage, and allowance for time-dependent variations. It is the understanding of the time-varying phenomena which is the subject of this study. Such phenomena occur due to the periodic interaction between stages in a turbine, either that of a nozzle guide vane on a rotor downstream or vice-versa. In most contemporary designs of turbines the effects are due primarily to the wakes from the trailing-edge of the upstream airfoil, and to any associated shock structures resulting from transonic exit flow Mach numbers. The present investigation is concerned with furthering knowedge of these wake and shock interactions, using a method of simulation established in the Isentropic Light Piston Tunnel and Oxford. Measurements of heat transfer rates and pressures are presented, supported by flow visualisation methods such as surface oil-dots and schlieren photography, for two examples of high-pressure turbine rotor blades. The majority of analysis deals with the first of these (a highty-loaded transonic profile) whilst the second blade (designed for use in a large civil engine) is included for investigation of the effects of flow unsteadiness on the film cooling process The transition process is examined in detail by use of wide bandwith heat transfer measurements, and a new method derived for modelling this process. It has been possible to observe the effect of the enhanced turbulence in the simulated nozzle guide vane wake and effects due a shock-boundary layer interaction. The reaction of the blade boundary layers to these disturbances is identified, and trajectories of disturbed events tracked along the blade surfaces. The measurements which have been taken allow for some aspects of wake and shock interactions to be included in the design process for turbine blading. A better understanding has been obtained of how these types of transient flow regimes affect the boundary layers on the blade surfaces.